2017
DOI: 10.1159/000486154
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid A Protects Against Diabetic Nephropathy through Ameliorating Glomerular Endothelial Dysfunction via Inhibiting AGE-RAGE Signaling

Abstract: Background/Aims: Glomerular endothelium dysfunction leads to the progression of renal architectonic and functional abnormalities in early-stage diabetic nephropathy (DN). Advanced glycation end products (AGEs) and receptor for AGEs (RAGE) are proved to play important roles in diabetic nephropathy. This study investigated the role of Salvianolic acid A (SalA) on early-stage DN and its possible underlying mechanism. Methods: In vitro AGEs formation and breaking rate were measured to illustrate the effect of SalA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…In addition, some commercial drugs approved by FDA were reported to show serious side effects, which severely impeded their clinical use, hinting new drugs and strategies are urgently needed [14][15][16]. In this review, we highlight a number of natural products that could target the above-mentioned mediators as exemplified by 25-O-methylalisol F [17], poricoic acid ZA [18] and salvianolic acid A [19], which might provide novel therapeutic strategy for the treatment of renal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some commercial drugs approved by FDA were reported to show serious side effects, which severely impeded their clinical use, hinting new drugs and strategies are urgently needed [14][15][16]. In this review, we highlight a number of natural products that could target the above-mentioned mediators as exemplified by 25-O-methylalisol F [17], poricoic acid ZA [18] and salvianolic acid A [19], which might provide novel therapeutic strategy for the treatment of renal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…15,20 Endothelial dysfunction leads to renal structural and functional abnormalities in DN. 21 We showed that a lack of Corin in HK-2 cells could attenuate endothelial migration of EA.hy926 cells through paracrine crosstalk that is likely mediated by ANP. Our previous studies on DCM revealed that Corin from cardiomyocytes affects endothelial cells in a similar fashion.…”
Section: Xue Et Almentioning
confidence: 78%
“…Although a lot of research has been done on the search of novel treatments for established DN [17][18][19], the development of tools for the early detection and prognosis of DN is needed in order to identify patients at risk and carry out interventional strategies to prevent the onset of DN. Several miRNAs have been related to the pathological mechanisms of DN [20]; for example, miR-192, which is specifically expressed in the kidney, is downregulated in patients with established DN, and has been related to increased fibrosis and reduced eGFR [21].…”
Section: Discussionmentioning
confidence: 99%